The Analysis of Financial Ratios, Good Corporate Governance, Reward, and Asymmetric Information in Earnings Management of Manufacturing Companies in Indonesia - Sagung Oka Pradnyawati; Ni Kadek Ayu Yuliantari; Ni Made Erna Wedayanti; Ni Luh Putu Yunita (AIBPM Publisher, 2024)
Earnings management is possibly incorrect when it has a negative impact on the corporation’s financial health. Several large companies were affected by earnings management cases. This study analyzes the direct impact of various factors such as financial ratios, good corporate governance (GCG), reward, and asymmetric information on earnings management practices, especially in manufacturing companies in Indonesia. Data was obtained from the financial reports of 65 manufacturing companies published on the Indonesian capital market, processed, and tested using regression analysis. The study shows that there is a positive impact of profitability on earnings management, but leverage and the board of directors have a negative impact on earnings management, while institutional ownership, independent commissioners, reward, and asymmetric information do not show any relationship with earnings management. These findings add empirical evidence regarding factors that directly impact earnings management practices and can serve as a reference for investment analysis by investors. Further research is recommended using different factors such as corporate value or factors that may influence the occurrence of earnings management practices, such as financial distress.